Improving Azo Dye Decolorization Performance and Halotolerance of Pichia occidentalis A2 by Static Magnetic Field and Possible Mechanisms Through Comparative Transcriptome Analysis - Wang, Xiaohan; Wang, Yumeng; Ning, Shuxiang; Shi, Shengnan; Tan, Liang (Frontiers in Microbiology, 2020)
A halotolerant yeast, Pichia occidentalis A2, was recently isolated that can decolorize various azo dyes. The azo dye decolorization performance of this strain was characterized, including the degradation pathway and detoxification effects of this yeast. Additionally, the effect of static magnetic field (SMF) on this decolorization process was investigated. Activities of key enzymes were analyzed to estimate the change of metabolic activity. Furthermore, possible mechanisms were analyzed through detecting differentially expressed genes between yeast A2 in the absence and presence of SMF. The results indicated that yeast A2 displayed the optimal decolorization performance when the concentrations (g/L) of glucose, (NH4)2SO4, yeast extract, and NaCl were 4.0, 1.0, 0.1, and ≤30.0, respectively. Meanwhile, the optimal rotation speed, temperature, and pH were 160 rpm, 30°C, and 5.0, respectively. ARB was decolorized and detoxified by yeast A2 through successive steps including cleavage of the naphthalene-amidine bond, reductive deamination, oxidative deamination/desulfurization, open-loop of hydroxy-substituted naphthalene and TCA cycle. Dye decolorization efficiency and halotolerance of yeast A2 were enhanced by 206.3 mT SMF. Activities of manganese peroxidases (MnP) and laccases (Lac) were elevated 1.37- and 1.16-fold by 206.3 mT SMF, but lignin peroxidases (LiP) activity showed little change. It was suggested from the transcroptome sequence that the enhanced halotolerance might be related to the up-regulated genes encoding the enzymes or functional proteins related to intracellular synthesis and accumulation of glycerol.